2018
DOI: 10.1016/j.matdes.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to rapidly generate random periodic representative volume elements for microstructural assessment of high volume fraction composites

Abstract: An algorithm based on event-driven molecular dynamics theory was developed to rapidly generate periodic representative volume elements (RVEs) with nonuniform distributions for both unidirectional fiber-reinforced and spherical particle-reinforced composites. Detailed statistical analyses were conducted for assessing the ability to generate RVEs with nonuniformly dispersed microstructures and either constant or random inclusion sizes for a wide range of volume fractions.The generated microstructures were direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Many studies [27][28][29][30] have simplified the fiber distribution into a periodic array of shapes, including rectangular, cylindrical, diamond, and hexagonal models. However, experimental studies [31][32][33] have found that fiber distribution does not always follow a perfectly uniform distribution. Therefore, in this paper, ABAQUS-PYTHON scripting is used to generate an RVE model in which the fibers and voids are randomly distributed in the matrix.…”
Section: Numerical Prediction Methodologymentioning
confidence: 99%
“…Many studies [27][28][29][30] have simplified the fiber distribution into a periodic array of shapes, including rectangular, cylindrical, diamond, and hexagonal models. However, experimental studies [31][32][33] have found that fiber distribution does not always follow a perfectly uniform distribution. Therefore, in this paper, ABAQUS-PYTHON scripting is used to generate an RVE model in which the fibers and voids are randomly distributed in the matrix.…”
Section: Numerical Prediction Methodologymentioning
confidence: 99%
“…Gaussian distribution of any random algorithm gives valuable information about the possibility and accuracy of the algorithm. [ 20 ] According to Figure 10, Gaussian fit curves for center coordinates in 3D signify the reliability of the generated RVE.…”
Section: Micromechanical Modelingmentioning
confidence: 99%
“…However, continuum approaches are more popular than MD simulations due to the high computational costs and complexity of MD methods. [18] To simulate three-dimensional micromechanical models in the finite element (FE) commercial software, extensive studies have been conducted to assess elastic properties of composites with a random distribution of fibers [19][20][21][22] or nanoparticles. [23] In this regard, several random geometry generation and distribution algorithms have been introduced by the scientific community in order to enhance the accuracy of analysis.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the prediction of the mechanical behavior of heterogeneous materials, recent studies have presented methodologies to create sub-volumes with random microstructures which attempt to capture the effects of fiber arrangement on the homogenized properties, and also on the distribution of the stresses at microscopic level [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. These approaches are very interesting from the point of view of more realistic representations when compared to classical periodic fiber arrangement.…”
Section: Introductionmentioning
confidence: 99%